+0  
 
0
83
1
avatar

Simplify \(\large \dfrac { \csc { \theta } }{ \sin { \theta } } - \dfrac { \cot { \theta } }{ \tan { \theta } } = \, ? \)

 Jun 26, 2020
 #1
avatar+21953 
0

csc(x)  =  1 / sin(x)

--->   csc(x) / sin(x)  =  [ 1 / sin(x) ] / sin(x)  =  1 / sin2(x) 

 

cot(x)  =  cos(x) / sin(x)

tan(x)  =  sin(x) / cos(x)

--->   cot(x) / tan(x)  =  [ cos(x) / sin(x) ] / [ sin(x) / cos(x) ]  =  cos2(x) / sin2(x)

 

So, we now have:  [ 1 / sin2(x) ] - [ cos2(x) / sin2(x) ]

--->                         [ 1 - cos2(x) ] / sin2(x)

--->                                  sin2(x) / sin2(x)  =  1 

 Jun 26, 2020

53 Online Users

avatar
avatar
avatar
avatar